Milo Talon - L'Amour, Louis (Toronto New York Bantam Books, 1981)
Milo Talon knew the territory and the good men from the bad. He had ridden the Outlaw Trail and could find out things others couldn$1 (Bt. That was why a rich man named Jefferson Henry hired Milo to hunt down a missing girl. But from the moment Milo began his search, he knew something wasn$1 (Bt right. Three people had already died, an innocent woman was on the run, and a once sleepy town was getting crowded with hired guns. Suddenly, Milo Talon realized that there were still things he had to learn$1 (Babout the woman he was trying to find, the man who had hired him, and the murderer who wanted him dead. But most of all, Milo had a few things to learn about himself. And he would have to work fast, because one mistake could cost him his life.s
89656